Optimalisasi Pengelolaan TPS 3R di Desa Batu Belah - Desrimon, Arfi; Islah, Muhammad; Putri, Bunga Deka (Journal of Social and Community Service, 2022)
This activity optimizes waste management based on TPS 3R (Reduce, Reuse, Recycle) in Batu Belah Village with an educational and participatory approach to support environmentally conscious development. The program is implemented as a form of support for reducing the volume of waste disposed of at the Final Disposal Site (TPA), while increasing public awareness in sorting and managing waste from its source. The methods used include a survey of the condition of TPS 3R, socialization to the community, and technical training on waste management according to the 3R principles. The results of the activity show that waste management at TPS 3R Batu Belah Village has not previously run optimally due to limited facilities, minimal community participation, and lack of education. Through this activity, there has been an increase in community knowledge, more active participation, and improvements to the waste collection and sorting system. This program is expected to be a model for other villages in implementing integrated and sustainable community-based waste management.